Chir Pine Forests of Western Himalaya are Under Stress Because of Combined Effects of Resin Extraction, Recurrent Fire and Climate Change: A View Point - Negi, G. C. S. (International Journal of Ecology and Environmental Sciences, 2024)
Pine (Pinus sp.) resin is a non-wood forest product used for multiple purposes worldwide since ancient times. Out of five Pine species occurring naturally in India (Himalayas), only Pinus roxburghii is tapped for resin using Rill method in Uttarakhand and Borehole method in Himachal Pradesh. The earlier faulty Cup-and-Lip method of resin extraction has been completely abandoned in this region for a few decades. The advantages and disadvantages associated with these two methods regarding the vulnerability of Pine trees to forest fire and consequent windfall have been discussed. In Uttarakhand, Pine forests spread over 4.12 lakh ha face colossal loss every summer due to recurrent fire of anthropogenic origin. Over the years, the faulty resin tapping practices are making trees vulnerable to forest fire and windfall. Further, climate change and human-caused forest fire has put the Pine forests under ever greater stress that has affected their natural structure and functioning and the ecosystem services, causing a considerable loss to the environment and economy of this region. The lack of enforcement of rules for resin tapping laid by the Forest Department has been highlighted as the main factor behind the vulnerability of the trees to fire and their subsequent windfall. This article examines the combined effects of resin extraction, forest densification, fire, and climate change on the Chir Pine forests of the western Himalayan region and underscores some research questions to be answered involving well-designed studies for managing these forests for ecosystem services and human well-being.